2018
DOI: 10.1007/s12265-017-9779-4
|View full text |Cite
|
Sign up to set email alerts
|

Computational Modeling for Cardiac Resynchronization Therapy

Abstract: Cardiac resynchronization therapy (CRT) is an effective treatment for heart failure (HF) patients with an electrical substrate pathology causing ventricular dyssynchrony. However 40–50% of patients do not respond to treatment. Cardiac modeling of the electrophysiology, electromechanics, and hemodynamics of the heart has been used to study mechanisms behind HF pathology and CRT response. Recently, multi-scale dyssynchronous HF models have been used to study optimal device settings and optimal lead locations, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 149 publications
0
35
0
Order By: Relevance
“…Computer simulation of the heart has emerged as a novel tool in cardiology research and its applications for CRT have already been reported [11]. Such applications include not only studies for understanding the mechanism of CRT and/or searches for optimal pacing strategies using standard heart models but also those attempting to predict therapeutic outcomes with patient-specific models, thus aiming at an alternative approach to patient selection [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Computer simulation of the heart has emerged as a novel tool in cardiology research and its applications for CRT have already been reported [11]. Such applications include not only studies for understanding the mechanism of CRT and/or searches for optimal pacing strategies using standard heart models but also those attempting to predict therapeutic outcomes with patient-specific models, thus aiming at an alternative approach to patient selection [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the models use a complex and accurate description of the ion currents and propagation of action potential along the heart chambers. Such models are useful for simulation of arrhythmias . However, only a very few patient‐specific models provide an adequate description of mechanics or electromechanics of cardiac muscle .…”
Section: Introductionmentioning
confidence: 99%
“…Such models are useful for simulation of arrhythmias. 3 However, only a very few patient-specific models provide an adequate description of mechanics 4 or electromechanics of cardiac muscle. 5 The major problems arise from the lack of information that can be obtained from clinical measurements for fitting numerous model parameters, especially their distribution in different regions of the heart.…”
Section: Introductionmentioning
confidence: 99%
“…As another limitation, these studies consider only elastic models for the myocardium, therefore, cannot not address the implications of viscosity on LV motion. In the second example, we present qualitative simulations of cardiac resynchronization therapy (CRT) in a continuously beating biventricle heart model generated from cardiac magnetic resonance imaging (cMRI) data. Most of the existing computational studies of CRT in the literature use weakly coupled algorithms . On the other hand, these studies mainly employ a monodomain model for the description of the electrophysiology.…”
Section: Introductionmentioning
confidence: 99%